Comparative study on salt stress response of Camelina sativa and Carthamus tinctorius during germination - Kukrić, Teodora; Marjanovic Jeromela, Ana; Nikolic, Zorica; Jovicic, Dusica (Journal of Agricultural Sciences (Belgrade), 2023)
Soil salinisation is one of the most significant global problems, leading to reduced agricultural productivity potential and biodiversity. The main salt commonly found on the surface of soils and in water is NaCl, which directly impacts plant growth and land degradation. Therefore, this study was conducted to examine the agronomic characteristics of two genotypes of Camelina sativa (’NS Slatka’; ’NS Zlatka’) and two genotypes of Carthamus tinctorius (’NS Lana’; ’NS Una’), which potentially seclude them as salt-tolerant crops. The levels of salinity tolerance were compared under five treatments of NaCl, ranging from 0mM to 200mM. Based on the obtained results, seeds of all four genotypes germinated at the highest salt concentration (200mM NaCl), but the germination percentage declined at all salt concentrations. Moreover, lower salt concentrations induced root elongation and reduced shoot length of seedlings of all four genotypes. Salt stress tolerance indexes showed the importance of equating the plant parameters into mathematical indexes, and the significance of comparing all the tolerance indexes according to salt stress.